2004
DOI: 10.1185/030079904x2763
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of anemia in patients with chronic kidney disease

Abstract: Anemia was present in 47.7% of 5222 predialysis patients with chronic kidney disease. Prevalence of anemia increased as kidney function decreased. Certain subgroups are at increased risk for anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
269
8
19

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(330 citation statements)
references
References 19 publications
19
269
8
19
Order By: Relevance
“…We observed a tendency toward gradual increased serum hemoglobin levels in all treated patients. This could be of clinical relevance given that the prevalence of anemia increases with deteriorating renal function 28 and is related to cardiac complications 29 and cerebrovascular events. 30 In this context, it is noteworthy that data from both experimental and human studies have suggested a role of renal sympathetic nerves in the modulation of erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a tendency toward gradual increased serum hemoglobin levels in all treated patients. This could be of clinical relevance given that the prevalence of anemia increases with deteriorating renal function 28 and is related to cardiac complications 29 and cerebrovascular events. 30 In this context, it is noteworthy that data from both experimental and human studies have suggested a role of renal sympathetic nerves in the modulation of erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia is a common finding in chronic kidney disease (CKD), affecting over half of all patients [1]. Diabetes, as the most common single cause of CKD in the Western world, is therefore also the most common cause of renal anaemia.…”
Section: Introductionmentioning
confidence: 99%
“…A nemia is commonly associated with chronic kidney disease (CKD) (1)(2)(3) and contributes to the morbidity and mortality and reduced quality of life in these patients (4 -10). Erythropoiesis-stimulating agents (ESA) and clinical practice guidelines have been beneficial in managing renal anemia (11)(12)(13)(14)(15), and anemia correction has been associated with improved patient outcomes (16,17).…”
mentioning
confidence: 99%